2016
DOI: 10.1186/s12879-016-1914-3
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of pneumococcal meningitis among older children (≥5 years) and adults after the implementation of an infant vaccination programme with the 13-valent pneumococcal conjugate vaccine in Ghana

Abstract: BackgroundAn outbreak of pneumococcal meningitis among non-infant children and adults occurred in the Brong-Ahafo region of Ghana between December 2015 and April 2016 despite the recent nationwide implementation of a vaccination programme for infants with the 13-valent pneumococcal conjugate vaccine (PCV13).MethodsCerebrospinal fluid (CSF) specimens were collected from patients with suspected meningitis in the Brong-Ahafo region. CSF specimens were subjected to Gram staining, culture and rapid antigen testing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 40 publications
(60 reference statements)
8
73
0
Order By: Relevance
“…The incidence of serotype 1 Sp fluctuated over time, with a decline in Sp1 coinciding with an increase in other pathogens. Similar waves of serotype 1 meningitis have been described in Ghana [14,37]. As observed previously, over one-third of Sp meningitis cases died in hospital despite receiving appropriate treatment with ceftriaxone; this highlights the importance of disease prevention to reduce morbidity and mortality.…”
Section: Discussionsupporting
confidence: 77%
“…The incidence of serotype 1 Sp fluctuated over time, with a decline in Sp1 coinciding with an increase in other pathogens. Similar waves of serotype 1 meningitis have been described in Ghana [14,37]. As observed previously, over one-third of Sp meningitis cases died in hospital despite receiving appropriate treatment with ceftriaxone; this highlights the importance of disease prevention to reduce morbidity and mortality.…”
Section: Discussionsupporting
confidence: 77%
“…Serotype 12F in particular is emerging as an important cause of invasive pneumococcal disease with the propensity to cause outbreaks. 10 The global resistance profile showed resistance to penicillin G, erythromycin, tetracyclin and trimethoprim-sulfamethoxazole, with PNSSP at 42.85%. These are the antibiotics commonly used in auto-medication as they can be obtained without prescription at non-conventional pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…9 Kwambana found that Pneumococci expressing the serotype 1 capsule dominated the West African pneumococcal meningitis outbreaks. 10 Some studies reported that strains isolated from the upper respiratory tract of subjects in the Center Region of Cameroon were relatively sensitive to β-lactamines. 11 The increasing resistance of S. pneumoniae to penicillin and other beta-lactamines raises enormous challenges in treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal population-specific vaccination strategies targeting outbreak control are needed. Additionally, preparation for future outbreaks in Africa as well as the Asia-Pacific region requires strengthened surveillance [50].…”
Section: Epidemics Outbreaks and Emergency Settingsmentioning
confidence: 99%